The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4274/tjo.38039
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Central Serous Chorioretinopathy

Abstract: Bullous central serous chorioretinopathy (CSCR) is a rare variant of CSCR characterized by severe serous retinal detachment which especially involves the inferior quadrants. Corticosteroid therapy administered for systemic or ocular misdiagnoses may induce and exacerbate CSCR. The purpose of this study was to report diagnosis and treatment results of an unusual case of bullous CSCR induced by systemic and periocular corticosteroid therapy received at another medical center due to a misdiagnosis of Vogt-Koyanag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Elimination of risk factors is advisable in bCSCR as in CSCR. In particular, systemic corticosteroid withdrawal is suggested as the first step, if possible, according to systemic conditions (e.g., previous organ transplant) [ 9 , 18 , 25 , 28 , 30 , 31 , 32 ]. Kunavisarut et al stopped steroid medication in six patients and tapered it in one (adding azathioprine).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elimination of risk factors is advisable in bCSCR as in CSCR. In particular, systemic corticosteroid withdrawal is suggested as the first step, if possible, according to systemic conditions (e.g., previous organ transplant) [ 9 , 18 , 25 , 28 , 30 , 31 , 32 ]. Kunavisarut et al stopped steroid medication in six patients and tapered it in one (adding azathioprine).…”
Section: Resultsmentioning
confidence: 99%
“…Cebeci et al combined PDT and laser photocoagulation with 25 mg oral eplerenone twice daily [ 31 ]. In particular, a patient affected by bilateral bCSCR was treated with reduced-fluence PDT (25 J/cm 2 , 3000 mW/cm 2 ) in the right eye (RE) seen at ICGA and with laser photocoagulation left eye (LE).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that glucocorticoids can reduce macular edema and aggravate SRF accumulation in CSC patients [ 6 ]. Additionally, in previous reports, the occurrence of bullous retinal detachment was also associated with a history of glucocorticoids [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 88%